2020
DOI: 10.1016/j.jot.2020.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells in knee osteoarthritis treatment: A systematic review and meta-analysis

Abstract: Summary Stem cells are considered to be one of the greatest potential treatments to cure degenerative diseases. Stem cells injection for knee osteoarthritis (OA) is still a relatively new treatment and has not yet gained popularity. So, the effectiveness, safety and potential of mesenchymal stem cells (MSCs) for knee OA treatment is worthy to be explored. Explore the effectiveness and safety of mesenchymal stem cells (MSCs) in the treatment of knee osteoarthritis. We collected clinical trials usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(113 citation statements)
references
References 47 publications
(130 reference statements)
0
111
0
2
Order By: Relevance
“…These observations were further reinforced in another meta-analysis including 19 studies (15 RCTs, 2 retrospective studies, and 2 cohort studies, of which 9 studies were with AD-MSCs, 5 with BM-MSCs, peripheral blood stem cells in 1 study, and MSCs from a fetus in 4 studies) that found statistically significant pain relief effectiveness measured by the VAS at 12 months’ and KOOS and WOMAC at 6 months’ follow-up. The included studies demonstrated no side-effects of intra-articular MSC therapy [ 102 ]. In a systematic review and meta-analysis by Maheshwer and colleagues including 25 studies, a different result was observed, as demonstrated by no significant pain improvement, but a functional and cartilage volume improvement (0.66 and 0.84 standardized mean difference (SMD), respectively) [ 103 ].…”
Section: Intra-articular Injectionsmentioning
confidence: 99%
“…These observations were further reinforced in another meta-analysis including 19 studies (15 RCTs, 2 retrospective studies, and 2 cohort studies, of which 9 studies were with AD-MSCs, 5 with BM-MSCs, peripheral blood stem cells in 1 study, and MSCs from a fetus in 4 studies) that found statistically significant pain relief effectiveness measured by the VAS at 12 months’ and KOOS and WOMAC at 6 months’ follow-up. The included studies demonstrated no side-effects of intra-articular MSC therapy [ 102 ]. In a systematic review and meta-analysis by Maheshwer and colleagues including 25 studies, a different result was observed, as demonstrated by no significant pain improvement, but a functional and cartilage volume improvement (0.66 and 0.84 standardized mean difference (SMD), respectively) [ 103 ].…”
Section: Intra-articular Injectionsmentioning
confidence: 99%
“…In human research, study results strongly suggest that MSC therapy is effective in relieving pain and improving joint function in patients suffering from OA. Especially the effect on knee OA has been investigated thoroughly (22)(23)(24). Moreover, since no obvious adverse effects are described, MSC use in humans might be a safe and effective alternative for current OA management therapies (22,23).…”
Section: Upcoming Importance Of Mesenchymal Stem Cells In the Osteoarthritis Research Fieldmentioning
confidence: 99%
“…Stem cells possess a therapeutic effect through differentiation ability, immunity regulation, antiinflammatory, improving microenvironmental conditions, and enhancing the regeneration process [25]. MSC have multipotent progenitor capabilities derived from adult stem cell (ASC) populations that can be found in some tissues such as bone marrow, peripheral blood, adipose tissue, synovium tissue and fluid, placenta, and umbilical cord.…”
Section: Stem Cells Therapy For Oamentioning
confidence: 99%